Pola Penyusunan Pesan Kebijakan Pemerintah Dalam Membangun Citra Direktorat Jenderal Perhubungan Laut : Studi Deskriptif Pada Instagram @djplkemenhub151 - Shaila Annisa Yahya; Tria Patrianti (STIKes Ibnu Sina Ajibarang, 2024)
Government content is not trusted by the public and is boring. Policies on government social media are not well socialized. This phenomenon makes the Directorate General of Sea Transportation's public relations adapt the trend for publishing policy message information. The aim of this research is to determine the pattern of preparing government policy messages in building the image of the Directorate General of Sea Transportation. The theory used in this research is message structuring theory. The theory consists of attention, need, satisfaction, visualization, action. This research use desciptive qualitative approach. Data collection techniques were carried out using in-depth interviews and documentation methods. In testing the validity of the data, a source triangulation test was carried out using in-depth interview techniques. The results of this research are that the pattern of preparing government policy messages on Instagram @djplkemenhub151 is quite good. This can be seen from the message preparation process carried out by the public relations team. The attention stage is found by determining the agenda setting, determining the type of Indonesian and English, the language is semi-formal, the factor that influences the message to attract attention is the trend. The need stage is carried out with research. determine the actual topic that is used as a message, and look for references in online media. The satisfaction stage is obtained by selecting the right visuals. The visualization stage was obtained through determining the visual characteristics of the bombang icon and determining the turquoise green display color. The action stage is that the public relations team carries out preparations and team discussions to compose the message. The interaction that is built is carried out by responding quickly and responsively to the hotline service or replying to comments. The conclusion from this research is that a good message structuring pattern can build a positive image of the Directorate General of Sea Transportation.